A LOOK AT THE NORMAL SCHOOL LIBRARY IN BRAZIL: LOCUS OF TEACHER FORMATION AND DISSEMINATION OF KNOWLEDGE - Pereira Sales, Giza Guimaraes [UNESP]; Castro, Rosane Michelli de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
For more than a century in Brazil, the Normal Schools were consolidated as the main institutions of teacher education. In order to understand how the process of formation of Primary teachers in the country occurred, between the mid-19th century and the end of the 20th century, in this text, aspects of the history of these institutions are resumed, and, with this, we seek to identify which importance existed the school libraries existing inside these schools and how they were constituted as a specific locus of training and knowledge. The proposal that demands the conduction of this discussion consists of analyzing specificities in relation to the Libraries of the Normal Schools, considered as centers of production and circulation of pedagogical knowledge essential for the formation of the future teacher.
Keywords: Teacher training; School library; Normal School